A ‘PERMA’ Response to the Pandemic: An Online Positive Education Programme to Promote Wellbeing in University Students - Morgan, Blaire; Simmons, Laura (Frontiers in Education, 2021)
Pre-existing issues regarding the wellbeing and mental health of university students have subsequently been compounded by the global COVID-19 pandemic. Research signals that anxiety and depression symptomology has increased in university students’ following the COVID-19 outbreak, and mental wellbeing has declined. In response to concerns around mental health of students in Higher Education (HE), and to support the transition to remote working during the pandemic, we designed and implemented an 8-week wellbeing programme based on positive education frameworks and practices. The online programme was delivered in a West Midlands-based university in the UK, to undergraduate and postgraduate psychology students. The weekly sessions (ran through a virtual learning environment (VLE)) aimed to i) provide students with a community and an opportunity to feel connected with other students, ii) introduce students to key concepts of wellbeing, and iii) equip students with knowledge and resources that would help sustain/improve their wellbeing. In this paper we outline how positive education, and specifically the ‘PERMA’ wellbeing framework, has inspired the development of this wellbeing programme (including the accompanying VLE webpages and sources of support) and future plans for evaluation. We further describe the content and delivery of this programme alongside practical implications, lessons learned and important constraints. We situate this discussion alongside consideration of ongoing wellbeing support requirements following the pandemic and issues regarding wider integration of PERMA approaches in university contexts.